Topological Hall effect arising from the mesoscopic and microscopic non-coplanar magnetic structure in MnBi. (March 2022) - He, Yangkun; Schneider, Sebastian; Helm, Toni; Gayles, Jacob; Wolf, Daniel; Soldatov, Ivan; Borrmann, Horst; Schnelle, Walter; Schaefer, Rudolf; Fecher, Gerhard H.; Rellinghaus, Bernd; Felser, Claudia
Abstract: The topological Hall effect (THE), induced by the Berry curvature that originates from non-zero scalar spin chirality, is an important feature for mesoscopic topological structures, such as skyrmions. However, the THE might also arise from other microscopic non-coplanar spin structures in the lattice. Thus, the origin of the THE inevitably needs to be determined to fully understand skyrmions and find new host materials. Here, we examine the Hall effect in both, bulk- and micron-sized lamellar samples of MnBi. The sample size affects the temperature and field range in which the THE is detectable. Although a bulk sample exhibits the THE only upon exposure to weak fields in the easy-cone state, in micron-sized lamella the THE exists across a wide temperature range and occurs at fields near saturation. Our results show that both the non-coplanar spin structure in the lattice and topologically non-trivial skyrmion bubbles are responsible for the THE, and that the dominant mechanism depends on the sample size. Hence, the magnetic phase diagram for MnBi is size-dependent. Our study provides an example in which the THE is simultaneously induced by two mechanisms, and builds a bridge between mesoscopic and microscopic magnetic structures.